Commercial Value of Likeness in the Spanish Legal System: Between the Protection of Personality and the Commercialization of ldentity (Communication & Society, 2000)
This article analyses the commercial value of the identity in the United States' legal system -the right of publicity- as well as in the Spanish one, in this case as a part of the right on the own likeness. Commercial aspects of the right on likeness have distinguished this right from others connected to it, and this have been a challenge for regulatory authorities. Taking as starting point the United States' regulation, which considers this right as a purely commercial one, it has been tried to go forward in the regulation of commercial aspects of likeness in Spain. It is pointed out, too, the incipient change in the commentators and sentences which goes further than the idea of likeness and seems to extend it into the concept of identity. The article concludes by stressing the contributions that United States' regulation could bring to the Spanish regulatory landscape.